DAMPAK PENGEMBANGAN SEKTOR EKONOMI TERHADAP POTENSI KONFLIK DI KPHP DELTA MAHAKAM DAN KPHL SUNGAI BERAM HITAM - Sylviani Sylviani; Elvida Yosefi Suryandari (Jurnal Penelitian Sosial dan Ekonomi Kehutanan, 2017)
Regional economic growth is determined by the potential of existing natural resources, including for fisheries and mining. The development of the two sectors also opens up potential for conflict with other sectors. The aim of the study is to determine the role of the sectors and the impact of economic growth to potential conflict in the research area. This research was conducted at Delta Mahakam Forest Production Management Unit (FPMU)and Sungai Beram Hitam Forest Protection Management Unit (FPMU) . Base sector approach was conducted to determine the superior sector by Location Quotient (LQ) using GDP variable. The results showed that at Delta Mahakam, mining sector was the dominant, and the second largest was fisheries with LQ ≥1. While at the Sungai Beram Hitam fisheries sector was the dominant sector,  and the mining sector was  non base since itsvalue ≤1. Process of forest area utilization for mining in Jambi was done through leasing of forest lands, but not in East Kalimantan. Conflict resolution between mining and fisheries sector with community was done through compensation. FMU status and position can be enhanced by granting authority on the leasing of forest area for strategic sector development and national interests.